Analisis Study Literatur Aplikasi Tik Tok Menjadi Penyebab Kasus Perceraian di Era Digital - Saputri Saputri; Zulham Zulham (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The development of the times that brings change can especially be felt with the presence of the media. Of course it is not surprising, knowing that social media is of great interest to digital technology users. However, the social media that is currently busy and popular among social media users, which is currently trending, is the Tik-Tok application. In the Tik Tok application, it displays a variety of videos that attract the attention of its users. But who would have thought, behind the use of the Tik Tok application as a means to increase creativity, it has a side that has an impact on users' feelings of addiction. Addiction is caused by Tik Tok users who do not have supervision or do not know the limits of excessive use. So, addicts to the Tik Tok application will be careless and even forget about how much time they use in their daily lives. This research aims to find out one of the causes of divorce caused by the TikTok application. So the application can be used as an anticipation of action for active social media users on the Tik Tok application. This research was prepared based on a library study taken from information related to the unwise use of Tik Tok which can give rise to bad habits such as bad morals, erosion of manners, neglect of carrying out obligations and not having a sense of responsibility.